Impact of Perinatal Death Auditing: Outcomes of An Interventional Study on Perinatal Death Auditing in Two Districts of Karnataka State, India - Harsha Kumar HN; Baliga, Shantaram B; Kushtagi, Pralhad; Kamath, Nutan; Rao, Suchetha S (National Journal of Community Medicine, 2025)
Background: Perinatal death auditing is useful to identify preventable perinatal deaths and avoidable/preventable factors. Objectives: To know the impact of perinatal death audit like 1). Documentation of Care Provided 2) Changes in Infrastructure and Facilities 3). Number of perinatal deaths 4) Any other impact. Methodology: Perinatal death auditing project implemented in two districts of Karnataka state. As a Part of Intervention, Expert Panel audited the perinatal deaths and provided feedback to the hospitals where these deaths occurred. The feedback included issues identified and suggestion for prevention. Trained Medical-Social Workers conducted evaluation surveys in post-interventional period at 6th monthly intervals. They collected the filled tools from the hospitals and handed over the written feedback of the expert panel to these hospitals. It was anticipated that the process of feedback would initiate some changes in infrastructure, facilities, documentation and number of perinatal deaths. Results: Number of reported perinatal deaths decreased in Koppal District (from 325 to 301) as compared with Dakshina Kannada (from 223 to 221). Improvements in: 1]. Documentation of care provided 2] Assertion of preventability by the doctors 3] Infrastructure &facilities were observed in backward district of Koppal as compared to developed district of Dakshina Kannada. Conclusion: Perinatal Death Auditing reduces the number of perinatal deaths apart from improving documentation, assertion of preventability by doctors, infrastructure & facilities.